Giuseppina Le Maire: passione civica, attivismo sociale, impegno educativo - Serpe, Brunella (Studi sulla Formazione/Open Journal of Education, 2013)
Giuseppina Le Maire's life and humanitarian, social and educational action have gone through maybe the most intense decades of italian history, from the proclamation of Italian unity to the forties of the twentieth century. Her commitment has made indelible tracks in many of the communities she reached; and of that commitment here is meant to give a first reconstruction.